Female Participation in Physical Education in Selected Primary School of Kashambya Sub-county Rukiga District. - Kyinkuhaire, Allen (Kabale University, 2025)
This study investigated female participation in physical education within selected primary schools of Kashambya Sub-county, Rukiga District. The research adopted a descriptive design and employed a mixed methods approach, integrating both quantitative and qualitative data collection tools. The sample size was 92 respondents, selected using stratified random sampling. Quantitative data was gathered using structured questionnaires, while interviews and focus group discussions provided qualitative insights. The study revealed that 65% of the respondents rated female participation in physical education as low or very low, with only 35% reporting moderate or high participation. Key factors influencing participation included socio-cultural norms (reported by 72% of respondents as highly influential), inadequate facilities (identified by 68% as inadequate), and low parental support (reported by 56% as unsupportive). The study concluded that addressing these barriers through gender-sensitive programs, improved facilities, and community awareness initiatives could significantly enhance female participation. The findings highlight the need for targeted interventions to bridge the gender gap in physical education within the study area. Recommendations include training for teachers, improving infrastructure, and involving parents in supporting girls’ participation in physical activities.